Pre-employment Quality Analisys through the Concept of Link and Match for SMK Teachers - Safrinanda Harahap; Rendyka Eliadi; Arif Boy Wilson (Universitas Muhammadiyah Enrekang, 2022)
The government has carried out a large-scale revitalization of vocational education tailored to the needs of industry and technological developments. Learning from industry players and industry practitioners is very important to be facilitated, including by increasing the weight of credits in learning from industry practitioners. There are eight aspects that need to be faced by the Indonesian vocational education world called Link and Match 8+i with industry. Industrial Work Practice is an educational, training, and learning activity for SMK (Vocational High School) students carried out in the business world or related industrial world with the competence of students according to the field they are engaged in. One of them is an Internship or Work Practice in the world of work for at least 1 semester. This aspect aims to encourage the quality of vocational school graduates to be in line with industry needs.